Glyphosate response in velvet bean developed in different temperatures (Research, Society and Development, 2021)
Velvet bean is an annual legume, which in recent years has assumed a prominent position as an important weed in several regions. Chemical control is one of the main tools for weed management, however, different climatic conditions can considerably influence the effectiveness of many molecules. Glyphosate is one of the systemic herbicides, with a wide spectrum of control, widely used for chemical control of weeds. Thus, the objective of this work was to evaluate the growth responses of velvet bean plants at different temperatures submitted to glyphosate doses. Two experiments were carried out in a greenhouse, in a completely randomized design, with five replications. The treatments consisted of nine doses of glyphosate (g ae ha-1) 2.81; 5.62; 11.25; 22.5; 45.0; 90.0; 180.0; 360.0 and 720.0, in addition to a control treatment (without herbicide application). Visual phytotoxicity evaluations were performed at 7, 14, 21 and 28 days after application (DAA), and at 28 DAA shoot dry matter of the plants, in addition to extraction and quantification of the epicuticular wax. Doses of glyphosate less than 22.5 g ae ha-1 did not cause any effect on plants and doses greater than 360 g ae ha-1 caused the death of the velvet bean in both experiments. The response of the velvet bean in the intermediate doses of glyphosate varied and was associated with the different temperature conditions that caused differences in the amounts of waxes in the experiments carried out. Velvet bean plants respond differently to the herbicide glyphosate under different temperature conditions.